Effect of different levels of phosphorus on growth and yield of wheat (Triticum aestivum L.) in Kandahar region of Afghanistan - Hikmatullah Obaid; Azizullah Khalili; Sharifullah Sharifi; Shiva Dhar (Annals of Agricultural Research, 2023)
A field experiment was carried out at Research Farm,Afghanistan National Agricultural Sciences and Technology University (ANASTU) Kandahar, Afghanistan, during within season of 2017-2018, to investigate the effect of different levels of phosphorus (P) on growth and yield of wheat (Shashambagh-08). The eight levels of phosphorus viz; 0, 15, 30, 45, 60, 75, 90 and 105 kg P2O5 ha–1 were tested in Randomized Complete Block Design (RCBD) in three replication. The Results revealed that there were significant differences in growth, yield attributes and yield of wheat due to phosphorus levels.Significantly superior plant height, dry matter accumulation, leaf area index, tillers m–2, length of spike, grains spike–1, grain weight spike–1, 1000-grain weight, grain yield, straw yield, biological and harvest index was observed with the application 90 kg P2 O5 ha–1. It is concluded that phosphorus application at the rate of 90 kg P2 O5 ha–1 was more conducive for recommendation for the farmers. The result also suggested that phosphorus at the rate of 60 kg P2 O5 ha–1 is frugal and affective rate for wheat, the application got intermediary more grain yield from wheat.